Perananan Kepala Desa dalam Pengembangan Desa Wisata - Helmita Helmita; Desi Derina Yusda; Oktavia Nila Sari (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
The role of the leader in Pujorahayu village greatly influenced progress and setbacks in the development of potential in the village. This research aims to: know the role of the village head, know the driving factors for the development of Pujorahayu Tourism Village; and know the inhibiting factors in the development of Pujorahayu Tourism Village. This study is a qualitative descriptor study. The subjects of the study were village heads, tourist village administrators, tourist conscious groups, PKK chairmen, cadet reefs, community leaders and tourist village communities selected by purposive sampling techniques. Data collection techniques use interviews, observations and literature studies. Data analysis techniques use qualitative descriptor analysis. The results showed that: the role of the village head as a leader in the village greatly influenced progress and setbacks in the development of potential in the village. In addition to being a leader in the government, the village head also has an important role in developing the potential of the village into an attractive tourist attraction in the village.